Prevalence of Impacted Mandibular Third Molars in Patients Aged 18–25 at Soelastri Dental Hospital - Pralampito, Firman Musti; Runting, Nina (Faculty of Dentistry, Universitas Islam Sultan Agung, 2025)
Background: Impacted teeth is defined by the teeth are block the path of normal eruption due to several factors such as lack of space in arch of jaw or begin an obstruction of the path of tooth eruption. Tooth eruption occur in more than one tooth. The third molar are the most frequently impacted and generally found at the age of 18-25 years. The initial examination to determine the impacted tooth is panoramic radiographic. Panoramic radiography was choosen because its convenient to use, minimal radiation dosage, and easy to see all condition the tooth in jaw stucture only in one film. This study aim to determine the prevalance of mandibular third molar impaction on panoramic radiography examination at RSGM Soelastri in the range of age 18 to 25 years.Method: The study type is observasional descriptive with longitudinal stiudy design. This design is look at the frequntly of mandibular third molar impaction case in the range of 18 to 25 years at RSGM Soelastri through panoramic radiography picture. This study use the secondary data from panoramic radiography soft file which available at radiography room at RSGM Soelastri in January 2021 to January 2022.Result: The result show that 81,2% the panoramic radiography picture there were impacted teeth where 27,4% were aged 18-19 years, 24.5% were aged 20-21 years, 22,2% were aged 22-23 years and 25,9% were aged 24-25 years.Conclusion: This study conclusion that prevalence of impacted third molar mandibular at RSGM Soelastri in patient where aged 18 to 25 years between January 2021 to January 2022 was 212 case of a total 261 panoramic radiography picture with a percentage of 81.22%.